Inpatient rehabilitation service utilization and outcomes under US ACA Medicaid expansion - Ying ( Jessica); Jing Nie; Katia Noyes (BMC, 2021)
Abstract Background To investigate the impact of the US Medicaid expansion on care utilization and health outcomes of patients treated in the inpatient rehabilitation facilities (IRF). Methods A retrospective observational study with a difference-in-difference design. The data was obtained from Inpatient Rehabilitation Facility - Patient Assessment Instrument (IRF-PAI). Sample included all Medicaid beneficiaries (aged 18-64 years) who received initial inpatient rehabilitation for stroke, hip fracture (acute conditions), or joint replacement (elective condition) (N = 14,917) before (2013) and after (2016) the expansion. The study estimated the differences in length of stay, functional improvement, and possibility of returning to community before and after ACA Medicaid expansion in the expansion regions relative to the non-expansion regions. The analysis was fully adjusted for patient demographics, health conditions, facility characteristics and time trends. Results Compared with non-expansion states, service volume in the expansion regions increased more for the two acute conditions (49 and 27% vs. 1% and − 4%) and decreased less for the selective condition (− 12% vs. -34%) after ACA Medicaid expansion. Medicaid expansion was associated with significant decreases in patient functional improvements (− 1.63 points for stroke, − 3.61 points for fracture and − 2.73 points for joint; P < 0.05). Length of stay and the possibility of returning to community after discharge were not significantly different. Conclusions Medicaid expansion was associated with increases in the utilization of inpatient rehabilitation services and decreases in the patient functional improvements. Cautions should be taken with the decreases in functional improvements among some subpopulation in the short-term; longer follow up periods are needed to account for gradual changes in patient needs.